Microwave-assisted extraction of phenolic compounds from moringa oleifera lam. leaves using response surface methodology as optimization tool - Sin, Kang (Animo Repository, 2014)
Microwave-assisted extraction (MAE) of phenolic compounds from the processed dry leaves of Moringa oleifera Lam. was optimized by applying response surface methodology. The phenolic profile and antioxidant activities of the extract obtained under optimum conditions were also evaluated. Optimum conditions for the extraction of phenolic compounds were achieved at 5 min of extraction time, 65 °C of extraction temperature, 0.015 g mL-1 of sample/solvent ratio and 35% of aqueous ethanol concentration. The yield of total phenolic content under optimum conditions was 16.5 ± 0.2 mg gallic acid equivalent (GAE) per g of dry leaf. The extraction yield was comparable with yield obtained by the conventional extraction technique. However, the technique was time efficient. The antioxidant activities were relatively high compared with those of some plants reported in the literature. Interestingly, the presence of vanillic acid, a new compound which had not been reported in M. oleifera in prior literature, was identified from the chromatogram for the dry leaf extract. The presence of the compound might be due to the lower destructive effect of MAE, at least, against vanillic acid.